2019
DOI: 10.1007/s12079-019-00540-8
|View full text |Cite
|
Sign up to set email alerts
|

ADP exerts P2Y12 -dependent and P2Y12 -independent effects on primary human T cell responses to stimulation

Abstract: Purinergic signaling plays a complex role in inflammation. Nucleotides released by T lymphocytes, endothelial cells, and platelets during inflammation induce cellular responses by binding to receptors that regulate intracellular signaling pathways. Previous studies have found that purinergic signaling can have both proinflammatory and anti-inflammatory effects, but the roles of specific pathways in specific cell types are poorly understood. We investigated the role of the P2Y 12 signaling pathway in the activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 53 publications
0
21
0
Order By: Relevance
“…Indeed, P2Y 12 receptor blockage influences T cell activation and cell proliferation. The effect of ADP is specific for CD4 and CD8 T cells, while P2Y 12 antagonism alters these effects, suggesting functional expression of P2Y 12 on T cells (Vemulapalli et al, 2019). We showed previously that silica-induced inflammation increased macrophage, neutrophil, dendritic cell, as well as lymphocyte infiltration (CD4 + and CD8 + ) in lung parenchyma (Moncao-Ribeiro et al, 2014).…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Indeed, P2Y 12 receptor blockage influences T cell activation and cell proliferation. The effect of ADP is specific for CD4 and CD8 T cells, while P2Y 12 antagonism alters these effects, suggesting functional expression of P2Y 12 on T cells (Vemulapalli et al, 2019). We showed previously that silica-induced inflammation increased macrophage, neutrophil, dendritic cell, as well as lymphocyte infiltration (CD4 + and CD8 + ) in lung parenchyma (Moncao-Ribeiro et al, 2014).…”
Section: Discussionmentioning
confidence: 73%
“…Purinergic signaling participates in IL-1β secretion by macrophages, as well as in NO production through P2X7 activation, as previously demonstrated by our group. On the other hand, P2Y 12 receptor does not participate in cytokine secretion (Vemulapalli et al, 2019), but its blockage significantly reduced NO and the pro-inflammatory mediators IL-6 and TNFα, due to reduced cellular recruitment.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The P2Y 12 receptor was originally sought to be exclusively expressed on platelets, with about 400 copies of the P2Y 12 receptor per cell, and to a lesser extent in subregions of the brain [11,15]. However, further studies demonstrated that P2Y 12 has a wider tissue distribution, being expressed and functional in microglial cells [16], vascular smooth muscle cells [17,18], and on several immune cells including dendritic cells [19], mast cells [20], eosinophils [21], monocytes [22], lymphocytes [23,24] and macrophages [25]. The P2Y 12 receptor expression has been also recently reported in osteoclasts [26] as well as in brain and breast cancer cell lines [27].…”
Section: Expression Of P2y 12 Receptormentioning
confidence: 99%
“…Micklewright et al demonstrated in human THP-1 monocytic cells that P2Y 12 was expressed and positively regulated P2Y6-mediated intracellular Ca 2+ signaling through suppression of adenylate cyclase activity [22]. Finally, Vemulapalli et al recently showed that functional P2Y 12 was expressed by T lymphocytes and that it exerted effects on biological responses of T cells when stimulated [23].…”
Section: Role Of Non-platelet P2y 12 Receptorsmentioning
confidence: 99%